Some Possibilities for Using Artificial Intelligence to Enhance the Curricula of Higher Education Institutions Training Professionals for the Real Estate Business - Stoencheva, Yana (Research Papers, 2025)
The article is dedicated to exploring the possibilities of using artificial intelligence to enhance the curricula of master’s degree programs in higher education institutions. In principle, this is a creative activity that must take into account a number of considerations—both formal, concerning the number and workload of academic courses, and substantive, related to building upon the foundation established in the bachelor’s degree. The process also involves aligning with practical needs, maintaining a forward-looking perspective based on new digital technologies, and ensuring the competitiveness and successful long-term professional realization of students.Based on a specific curriculum, a comparative analysis with other higher education institutions was conducted, along with a pilot survey among industry professionals. The requirements of the National Evaluation and Accreditation Agency, the qualification profile of the studied program, and the regulatory framework of the respective university were also taken into account. An algorithm for the use of publicly accessible artificial intelligence tools was developed and tested to generate ideas for integrating all the mentioned requirements. The obtained results are applicable for improving any other master’s degree curriculum in higher education institutions in Bulgaria.
Keywords: Education; Curriculum; Comparative analysis; Survey research; Artificial intelligence